On the trail of Sisyphus – addiction as an existential neurosis? - Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2023)
In Greek mythology, Sisyphus, king of the Corinthians, dared to deceive the gods and was condemned to roll a boulder to the top of a mountain for all eternity. Shortly before reaching the summit, however, the boulder rolled back down into the valley, and the arduous task had to begin anew. Many of the contents of this classic myth are reminiscent of the therapeutic approach to addictive disorders. In addiction therapy, too, it is often a long and rocky road that ends with a relapse. The therapeutic effort was not entirely in vain, but one often begins to doubt its usefulness. In terms of Sisyphus and a Bio-Psycho-Social Model (BPSM) of health and disease, addiction can be located at the end of a downward spiral. By extension of the BPSM, can addictive disease be considered an expression of existential neurosis? The results of our own research speak in favor of this and show a clearly reduced experience of sense and meaning, but also diminished feelings of hope and forgiveness in addiction patients.However, positive correlations between various parameters of existential well-being and mental health or more appropriate stress coping are also found for the addiction group. These results are supported by neuronal correlates and are mirrored in the general population. Based on this, the consideration of existential issues in addiction therapy can be discussed. Finally, the use of art therapy and work training are proposed as examples of a meaning based therapeutic intervention in dealing with people with addictive diseases.